Local failure resistance of polypropylene fiber reinforced concrete plates subjected to projectile impact. Issue 2 (June 2022) - Beppu, Masuhiro; Mori, Koki; Ichino, Hiroyoshi; Muroga, Yoichiro
This study investigated local failure characteristics of polypropylene fiber reinforced concrete (PPFRC) plates subjected to projectile impact. Flexural and compression tests for two types of PPFRC specimens (PPFRC1 and PPFRC2) were conducted to examine mechanical properties of the PPFRC. The average flexural strength of PPFRC1 and PPFRC2 at a strain rate of 10 −1 /s were 12.2 N/mm 2 and 10.4 N/mm 2, respectively. The average compressive strength of PPFRC1 and PPFRC2 at a strain rate of 10 0 /s were 58 N/mm 2 and 74.9 N/mm 2, respectively. Projectile impact tests for 60 mm- and 80 mm-thick PPFRC plates were conducted by using a 50 g-mass projectile collided at velocities corresponding to 193–423 m/s. Experimental results exhibited that the PPFRC plate had a higher effect of suppressing local failure than a plain concrete plate. Comparison of the tests results with the modified NDRC formula revealed that the limit scabbing thickness was 15–20% smaller than that of a plain concrete plate.